Mapping Machine Learning Trends in Chemistry Research using LLM with Multi-Turn Prompting - Yudertha, Andreo; Putri, Riski Dwimalida (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
A review of research in the field of chemistry that incorporates machine learning is essential to identify recent developments and explore its potential applications. Published research articles provide an opportunity to analyze emerging research trends. The use of natural language processing (NLP) technology not only accelerates text data analysis but also enhances accuracy in understanding the content and context of scientific articles. Previously, trend analysis in ophthalmology research had been conducted using Zero-Shot Learning. In this study, an analysis of chemistry-related articles focusing on machine learning was carried out using a multi-turn prompting technique. The process began with data collection through web scraping of abstracts containing the keywords